A dual-band circularly polarized microstrip patch antenna with a cross shaped slot for 0.92/2.45 GHz RFID applications - Matsunaga, Mayumi (IEICE COMMUNICATIONS EXPRESS, 2017)
A double-band circularly polarized (CP) patch antenna is presented. It is a round patch antenna with a cross-shape slot. Furthermore, it radiates wide beam CP waves at two radio-frequency identification (RFID) bands: 920 MHz and 2.45 GHz. Slightly oblate round patch antennas generally radiate CP waves and have resonant frequencies at two or more harmonic bands. To radiate wide beam CP waves at two bands, a cross-shape slot was made on a round patch antenna in this study. As a result, the cross-shape slot has made it possible for a 920 MHz round patch antenna to simultaneously radiate wide beam CP waves at 2.45 GHz which is higher than a harmonic frequency.